Discursos y prácticas de participación política de las personas con discapacidad del distrito metropolitano de Quito, de enero a junio del 2016 - Navarrete Valenzuela, Sammy Larry (2016)
The objective of this research: "Knowing the discourses and practices about the political participation of people with disabilities in the province of Pichincha, and particularly in the Metropolitan District of Quito from March to July 2016." The methodological perspective with no experimental but kind exploratory design was used. Applying Semi-structured interviews analyzed using a priori categories and emerging topics. Sample; 1) person with disabilities who belong to groups, associations or foundations of persons with disabilities, 2) persons with disabilities belonging to a foundation, and; 3) persons with disabilities acquired during the course of the last decade that participates in meetings and neighborhood training. This research brought about results; • The discourse of political participation of people with disabilities is under construction. • The practices of political participation of people with disabilities depend on the levels of accessibility political practices of people without disabilities offered. • They not yet have built political practices of people with disabilities, specific elements of universal accessibility. • People with disabilities perceive that they are not consulted in drafting legislation, plans and projects for people with disabilities.